STUDI KASUS PASIEN FRAKTUR TERTUTUP CLAVIKULA DEXTRA DENGAN NYERI AKUT - Trisya Yona Febrina; Hidayat Hartanto Permana; Isna Aglusi Badri (Ensiklopedia of Journal, 2023)
The World Health Organization (WHO) records that more than 5 million people die each year and about 1.3 million people experience physical disability due to closed fractures. The purpose of this study was to carry out nursing care for closed fracture patients at Mr. J and Mr. A with acute pain problems in the Emergency Installation (IGD) Embung Fatimah Hospital, Batam City. The research includes descriptive research with a case study design that was conducted for one day on two patients with the same nursing problems and cases, namely patients with closed clavicle fractures. Assessment data obtained in patients with closed clavicle fractures with acute pain problems, namely, both patients experienced signs and symptoms of pain in the shoulder, body felt weak, dizziness. The author formulates a diagnosis that is acute pain associated with displacement of bone fragments. Nursing planning for both patients is the same, namely to overcome my pain. Nursing actions have been given as needed. Based on nursing care carried out for 2 × 60 minutes, the results obtained that the problem in both patients was resolved and underwent treatment in the inpatient room. For this reason, it is hoped that this study can add insight to the family/patient in reducing complications or the risk of closed clavicle fractures.